2013
DOI: 10.1021/ma401260d
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Dangling Chains on Molecular Dynamics of Polyurethanes

Abstract: The effect of dangling chains on phaseseparated microstructure and molecular dynamics for polyurethanes (PUs) was investigated. PUs with different dangling chain lengths and polar groups were prepared through changing the types of diol extender. The molecular dynamics was studied by a combination of dynamic mechanical analysis (DMA) and broadband dielectric relaxation spectroscopy (BDRS). Four relaxations (processes), namely, a secondary relaxation (β), the soft phase segmental relaxation (α), the I process as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
61
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 63 publications
(62 citation statements)
references
References 51 publications
0
61
1
Order By: Relevance
“…As a rule, the damping properties of polymer materials are derived from internal friction caused by molecular chain movement and the destruction and regeneration of physical bonds between molecules . Therefore, the dangling chain can increase the internal friction between the molecular chain and improve the damping property of polymer by hindering the motion of main chain of polymer with dangling chain.…”
Section: Results and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…As a rule, the damping properties of polymer materials are derived from internal friction caused by molecular chain movement and the destruction and regeneration of physical bonds between molecules . Therefore, the dangling chain can increase the internal friction between the molecular chain and improve the damping property of polymer by hindering the motion of main chain of polymer with dangling chain.…”
Section: Results and Analysismentioning
confidence: 99%
“…As a rule, the damping properties of polymer materials are derived from internal friction caused by molecular chain movement and the destruction and regeneration of physical bonds between molecules. 41,42 Therefore, the dangling chain can increase the internal friction between the molecular chain and improve the damping property of polymer by hindering the motion of main chain of polymer with dangling chain. Figure 7 gives the dynamic mechanical spectra of PVAc with various dangling chains in a temperature range −100-100 C. As we know, the damping temperature range corresponds to that temperature range when tan δ value is more than or equal to 0.3.…”
Section: Effect Of Dangling Chain Length On Damping Property Of Develmentioning
confidence: 99%
“…The T g of the soft segment was observed in each sample and decreased from −49.6 to −56.5°C with increasing TMPM content. This may have been due to the plasticizing effect of long side chains . The long‐branched aliphatic chains hindered the close aggregation of soft segments and facilitated the movement of the chain segments.…”
Section: Resultsmentioning
confidence: 99%
“…There are a lot of researches about polyurethane containing the dangling chain have been reported [2][3][4][5] . Xu et al [6] fabricated segmented PUs with six-carbon dangling chain, they found that the presence of the six-carbon short dangling chain in each repeating unit of the soft segments does not limit the overall bulk properties.…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al [6] fabricated segmented PUs with six-carbon dangling chain, they found that the presence of the six-carbon short dangling chain in each repeating unit of the soft segments does not limit the overall bulk properties. Yu et al [2] synthesized PUs with different dangling chain lengths and polar groups, their research results show that the Tg of the PU shifted to lower temperature with increasing dangling chain length. When the danling chain is introduced into the polymer, the arrangement regularity between molecules will be disturbed so as to reduce the intermolecular stacking.…”
Section: Introductionmentioning
confidence: 99%